Embryonic Stem Cells A Practical Approach - Notarianni, Elena;Ed. Evans, Martin J;Ed (Practical approach series., 2006)
This book serves as a primer to ES cells, their derivation and experimental manipulation. It contains a broad compendium of methods of direct relevance to both graduate students and specialist researchers. An introductory chapter by the principle originator of ES cell research outlines the fundamentals and charts the development of the field. This is followed by comprehensive coverage of state-of-the art techniques for ES cell manipulation, with the mouse as the experimental paradigm, and by recent innovations with ES cells from human and non-human primates. ES cell-based therapies for otherwise intractable diseases are now being developed with the present challenge to control ES cell growth and differentiation for applications such as cell transplantation - a recurrent theme in this book. As a volume in the Practical Approach Series, the emphasis is on current methods from recognised experts.